2004
DOI: 10.1073/pnas.0402069101
|View full text |Cite|
|
Sign up to set email alerts
|

NF-κB-mediated repression of growth arrest- and DNA-damage-inducible proteins 45α and γ is essential for cancer cell survival

Abstract: The NF-κB/IκB signaling pathway is a critical regulator of cell survival in cancer. Here, we report that combined down-regulation of growth arrest- and DNA-damage-inducible proteins (GADD)45α and γ expression by NF-κB is an essential step for various cancer types to escape programmed cell death. We demonstrate that inhibition of NF-κB in cancer cells results in GADD45α- and γ-dependent induction of apoptosis and inhibition of tumor growth. Inhibition of GADD45α and γ in cancer cells by small interfering RNA ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
187
2
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 148 publications
(195 citation statements)
references
References 27 publications
5
187
2
1
Order By: Relevance
“…Also, using the gadd45aÀ/À mice, it has been reported that gadd45a promotes UV-induced apoptosis in skin keratinocytes (Maeda et al, 2002). Additional evidence for a proapoptotic function of gadd45a and gadd45g has been documented recently using either overexpression of these proteins in prostate and breast cancer cell lines or siRNA-mediated knockdown that was observed to block IkB-mediated apoptosis in these cell lines (Zerbini et al, 2004). On the other hand, our results are consistent with an earlier report where it was shown that p53 null MEFS that lack gadd45a are sensitized to UV-and cisplatin-induced cell death (Smith et al, 2000).…”
Section: Discussionmentioning
confidence: 87%
“…Also, using the gadd45aÀ/À mice, it has been reported that gadd45a promotes UV-induced apoptosis in skin keratinocytes (Maeda et al, 2002). Additional evidence for a proapoptotic function of gadd45a and gadd45g has been documented recently using either overexpression of these proteins in prostate and breast cancer cell lines or siRNA-mediated knockdown that was observed to block IkB-mediated apoptosis in these cell lines (Zerbini et al, 2004). On the other hand, our results are consistent with an earlier report where it was shown that p53 null MEFS that lack gadd45a are sensitized to UV-and cisplatin-induced cell death (Smith et al, 2000).…”
Section: Discussionmentioning
confidence: 87%
“…Also, using the gadd45a-/-mice, it has been reported that gadd45a promotes UV induced apoptosis in skin keratinocytes (57). Additional evidence for a pro-apoptotic function of gadd45a and gadd45g has been documented using either overexpression of these proteins in prostate and breast cancer cell lines or siRNA-mediated knockdown that was observed to block IkB mediated apoptosis in these cell lines (58). On the other hand, our results are consistent with an earlier report where it was shown that p53 null MEFS that lack gadd45a are sensitized to UV and cisplatin induced cell death (24).…”
Section: Hematopoietic Cells From Gadd45a and Gadd45b Deficient Mice mentioning
confidence: 95%
“…Whereas GADD45α and GADD45γ are strictly proapoptotic proteins [23,31], the involvement of GADD45β in the apoptotic process is debated. The present study demonstrates an anti-apoptotic effect of Gadd45b expression in beta cells exposed to IL-1β, and we have previously shown that enhanced Gadd45b expression prevents apoptosis [22,24,32] in other cell types.…”
Section: Discussionmentioning
confidence: 99%